Laser-induced transformation of graphene into graphene oxide nanospheres (GONs). (July 2019) - Yogesh, Gaurav Kumar; Gumpu, Manju Bhargavi; E.P., Shuaib; Sastikumar, D.
Graphical abstract: Scheme: Graphene nanosphere obtained through pulsed laser ablation of graphene without utilizing the template. Highlights: Template free synthesis of GO nanospheres (GONs) using laser ablation technique. Mechanism of Laser Induced transformation of GO to GONs has been studied. Fluorescent properties of GONs has been explored. Microstructural and functional analysis of GONs has been carried out. Abstract: In this work, we report a template-free synthesis of graphene oxide nanosphere (GONs) by the laser ablation of graphene in ethanol. The GONs were formed by crumpling of graphene sheet under the infrared nanosecond pulsed laser irradiation. FESEM and HRTEM images of as-prepared GONs were recorded to analyse the morphological characteristics. Raman, X-ray photoelectron and FTIR spectroscopy results confirmed the formation of GONs under the laser ablation. GONs exhibited the particle size ranges from 100 nm to 700 nm and the average particle size was estimated to be around 137 nm by particle size analyser. Photoluminescence study revealed bright blue-green PL emission under the excitation wavelength of 320–420 nm for GONs.